2012
DOI: 10.1002/pon.3023
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for psychological distress related to diagnosis of breast cancer

Abstract: These results suggest that intensive psychological intervention is necessary for breast cancer patients with large tumors, as well as for women with suspected breast cancer with high HADS scores at pre-consultation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 43 publications
3
26
0
4
Order By: Relevance
“…The sources of distress were fairly consistent with other published studies (Agarwal et al, 2013; Andreu et al, 2012; Harrington, Hansen, Moskowitz, Todd, & Feuerstein, 2010; Iwatani et al, 2013; Liao et al, 2013) in their type and frequency of occurrence. A cluster of symptoms (e.g., fatigue, worry, sleep, nervousness) were identified in 48%–56% of breast cancer survivors in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The sources of distress were fairly consistent with other published studies (Agarwal et al, 2013; Andreu et al, 2012; Harrington, Hansen, Moskowitz, Todd, & Feuerstein, 2010; Iwatani et al, 2013; Liao et al, 2013) in their type and frequency of occurrence. A cluster of symptoms (e.g., fatigue, worry, sleep, nervousness) were identified in 48%–56% of breast cancer survivors in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Distress is highest in the diagnostic phase of the breast cancer trajectory (Agarwal et al, 2013; Head et al, 2012; Knobf et al, 2013) and is also associated with down regulation of immunity (Andersen et al, 1998). Distress is also associated with trait anxiety (Ando et al, 2011; Iwatani, Matsuda, Kawabata, Miura, & Matsushima, 2013) and lack of confidence in support systems (Harding, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Various factors are predictive of emotional distress, including tumor stage, young age, disturbance related to changes in body image, and form of treatment (receiving chemotherapy rather than radiation therapy). Body‐related distress specifically related to hair loss from chemotherapy, mastectomy, and body weight changes following diagnosis and treatment is a well‐documented phenomenon reported by many breast cancer patients …”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that approximately 35% of patients with cancer experienced significant distress (Zabora et al, 2001). Prospective study showed that anxiety and depression were prevalent at diagnosis of cancer (Gil et al, 2012;Iwatani et al, 2013). Over 1/3 of patients newly diagnosed with esophageal cancer suffered from significant psychological symptoms, particularly anxiety (Bergguist et al, 2007;Dempster et al, 2012).…”
Section: Introductionmentioning
confidence: 99%